Mini Tuber Production in Potato Via Aeroponic System - Hussein Abdullah Ahmed AHMED; Serkan URANBEY; Nilüfer KOÇAK (Türkiye Tarımsal Araştırmalar Dergisi, 2018)
The aeroponic production system is one of the new applications in soilless agriculture. This system is also an alternative seed production system for mini-tuber production of potato in terms of providing optimum growth conditions, enabling potato production to be free from diseases and pests and to make economic use of agricultural inputs. This system, which is independent of climatic conditions, has the advantage of improving the vegetative growth, delaying tuber formation, prolonging the vegetative period, increasing the tuber yield per plant and total tuber yield while decreasing the tuber weight. Due to the problems experienced in potato seedling tuber production in recent years, it emerged as an alternative production system for our country.